Synthesis and anti-cancer activity of chiral tetrahydropyrazolo[1,5-a] pyridine-fused steroids - Lopes, Susana M. M. (2019)
Regio-and stereoselective synthesis of novel chiral 4,5,6,7-tetrahydropyrazolo [1,5-a]pyridine fused steroids via [8 pi + 2 pi] cycloaddition of diazafulvenium methides with steroidal scaffolds is reported. The biological evaluation of the new family of hexacyclic steroids as anti-cancer agents was also carried out. Hexacyclic steroids bearing a benzyl group at C-22, derived from 16-dehydropregnenolone and 16-dehydroprogesterone, show considerable cytotoxicity against EL4 (murine T-lymphoma) in contrast with the corresponding C-22-unsubstituted derivatives showing low cytotoxicity. Thus, results indicate that the presence of the benzyl group is important to ensure cytotoxicity.